Diagnóstico nutricional de macronutrientes en ananas comosus l. merr. var. roja trujillana en el valle santa catalina, La Libertad - Reyes Gerónimo, Juan Climaco (2016)
The research is conducted November 2014 to March 2015, with the aim of obtaining the nutritional diagnosis of macronutrients in Ananas comosus L. Merr. Var. Roja Trujillana in the Santa Catalina Valley, La Libertad. 11 Analysis of water, soil 33 and 33 foliar They were held in the towns of Laredo, Puente Arquito, Shiran, Poroto, Canseco, Concon, Platanar, Guayabito, Samne, Rayampampa and Plazapampa. The soil and leaf samples were taken from pineapple fields first, second and third production year Roja Trujillana pineapple. (i) The irrigation water with a pH of 6.41 and an electrical conductivity of 0.71 dS/m provides average per hectare of 0 a 7 Kg of NO3-, 160-1455 Kg of K, 418-2070 Kg of Ca, 121-700 Kg of Mg and 262-1394 Kg of S Roja Trujillana cultivation of pineapple in the Santa Catalina Valley. (ii) 33 soil samples tested, 97% are poor in organic matter, 76% of medium to high in phosphorus available, 85% of medium to high in potassium available, 97% of medium to high in calcium and changeable 100% rich in magnesium changeable at pH 5.28 and 1.56 dS/m of C. E. averages. (iii) From 33 leaf samples of Roja Trujillana pineapple evaluated, 82% are deficient in N, 30% P deficiency, K deficiency 91%, 55% Ca deficiency, Mg deficiency 82% and 91% deficiency S. levels are more generalized deficiency of N, K, Mg and S; lower levels of deficiency is present in P and Ca. On average primary macronutrients Guayabito is the only locality with normal foliar levels (1.36% N, 0.1% P and 2.1% K), the less fertilized, and Poroto is the only town with deficient levels (1.02% N, 0.07% P and 1.23% K), the most fertilized. In secondary macronutrients any location presents normal foliar levels; Shiran locations, Concon and Guayabito have all foliar deficient levels (0.215% Ca, Mg 0.13% and 0.05% S) and the remaining localities are deficient in at least one element. With growing age gaps increase in the cultivation of pineapple Roja Trujillana in the first campaign greatest deficiency of N, K and S is presented in the second campaign of N, K, S and Mg and the third campaign N, P, K, Ca, Mg and S.